Language and Emotion in Syair Pelarian dari Kejaran Opas: A Psycholinguistic Study - Yuzi Febriani; Bahren Bahren (Jurnal Vokasia, 2026)
This study analyzes the expression of emotion in the poem "Escape from the Pursuit of Opas" by Syekh Sidi Jamadi using a psycholinguistic approach using the Sapir–Whorf perspective that emphasizes the relationship between language and thought. The research problem focuses on how the language used in the poem reflects the poet's psychological condition, emotional experiences, and inner struggles when facing social pressures and colonial threats. Previous studies have mostly discussed classical poetry from the aspects of stylistics, semiotics, religion, and phonology, but have not examined the relationship between language and the poet's inner state psycholinguistically, so there is a gap that needs to be filled. This study aims to understand how language choices convey emotions such as fear, anxiety, despair, resignation, and hope. The method used is descriptive qualitative with data in the form of verses of the poem analyzed through in-depth reading, identification of emotional diction, and contextual interpretation. The results of the study show that the poet's language through repetition, metaphor, and choice of emotionally rich diction reflects his inner state and thought process. This study confirms that language does not only function to narrate external events, but also to represent psychological and emotional experiences, demonstrating the relevance of the Sapir–Whorf hypothesis in understanding the cognitive and affective dimensions of traditional Minangkabau poetry. Keywords: psycholinguistics, Sapir–Whorf, emotion, classical literature, poetry